The effect of sleeping posture on occupant injury in frontal coach crashes - Sun Tingting; Zaidi Mohd Ripin; Chan Ping Yi; Mohamad Ikhwan Zaini Ridzwan (Scientific Reports)
Abstract The safety of coaches in frontal crashes is attracting attention in various countries. Coach crash studies are done based on standard postures. Occupants travelling long distances in coaches may fall asleep, with postures that can be different from the standard posture. This paper investigates the effects of different sleeping postures on occupant injuries in frontal coach collisions by using sled test model and dummies. Four different sleeping postures are considered including head tilted sideway, slide down on seat in neutral position, turned torso-head diagonal with backrest and turned torso-head perpendicular with backrest posture. The results showed that the head tilted sideway posture increases occupant head injuries with the Head Injury Criteria (HIC) values of 399.3 to 494.6 and the peak head acceleration over 3 milliseconds (H3ms) reaches a maximum of 88.53 g which is above the accepted threshold of 80 g. Slide down on seat in neutral position posture reduces occupant head injuries where the HIC decreased by 28.47%, and for H3ms the decrease is 12.15%. Turned torso posture reduces neck injuries, and all those four sleeping postures are beneficial to reduce thorax injuries. The different turned torso postures simultaneously include the lowest risk and the highest risk postures.